Fuzzy logic controller for three‐level shunt active filter compensating harmonics and reactive power. (2nd November 2015) - Saidi, Salem; Abbassi, Rabeh; Chebbi, Souad
Summary: In this paper, the use of a three‐level inverter as a shunt active power filter is carried out, taking advantage of the benefits of multi‐level inverter, namely, the reduction both in the overall switching losses and in total harmonic distortion. The main focus of this article is to investigate the potentialities of the inverter employed as shunt active power filter on the compensation of the reactive power and the mitigation of harmonics drawn from a nonlinear load and unbalanced sources. The most previously reported three‐level inverter‐based shunt active power filters have been controlled and monitored through conventional controllers, which require a complicated mathematical model. In order to overcome this problem, an extended intelligent controller is proposed for a three‐level shunt active power filter. The aim of the proposed fuzzy logic control algorithm is to improve the behavior of voltage across the floating capacitors in steady/dynamic states and to minimize the switches commutations by taking into account the references of the harmonic currents injected in the network. The proposed control strategy has been simulated, and the obtained results prove that it is very successful. Copyright © 2015 John Wiley & Sons, Ltd.